Modelling alternative harvest effects on soil CO2 and CH4 fluxes from peatland forests - Li, Xuefei; Markkanen, Tiina; Korkiakoski, Mika; Lohila, Annalea; Leppänen, Antti; Aalto, Tuula; Peltoniemi, Mikko; Mäkipää, Raisa; Kleinen, Thomas; Raivonen, Maarit (Elsevier, 2024)
Over the last century, many peatlands in northern Europe have been drained for forestry. Forest management with different harvesting regimes has a significant impact on soil water status and consequently on greenhouse gas emissions from peat soils. In this paper, we have used the process-based JSBACH-HIMMELI model to simulate the effects of alternative harvesting regimes, namely non-harvested (NH), selection harvesting (SH; 70 % of stem volume harvested) and clear-cutting (CC; 100 % of stem volume harvested), on soil CH4 and CO2 fluxes in peatland forests. We modified the model to account for the specific characteristics of peatland forests, where the water level (WL) is generally low and is regulated by the amount of aboveground vegetation through evapotranspiration. Multi-year measurements before and after the forest harvesting in a nutrient-rich peatland forest in southern Finland were used to constrain the model. The results showed that the modified model was able to reproduce the seasonal dynamics of water level, soil CH4 and soil CO2 fluxes under alternative harvesting regimes with reasonable accuracy. The averaged Pearson's r (Pearson correlation coefficient) and RMSE (Root Mean Square Error) between the model and the measurement were 0.75 and 7.3 cm for WL, 0.75 and 0.23 nmol m−2 s−1 for soil CH4 flux, 0.73 and 0. 88 μmol m−2 s−1 for soil CO2 flux. The modified model successfully reproduced soil CH4 uptake at both NH and SH sites and soil CH4 emission at the CC site, as observed in the measurements. Our study showed that increasing harvesting intensity (NH → SH → CC) in the model increased soil CH4 emission and decreased soil CO2 emission on an annual basis, but the magnitude of the decreased soil CO2 emission was much larger than that of the increased soil CH4 emission when comparing their global warming potentials. Therefore, in the short term as in our study (first three years after the harvest), the climate impacts of the soil GHG was reduced more in CC than in SH, which yet can be fundamentally different when considering in the long term.
Keywords: peatland forests; alternative harvesting regimes; modelling; soil CH4 flux; soil respiration; water level